Classification of Intraocular Lenses - Vaibhav Nagpal (Delhi Journal of Ophthalmology)
This article aims at providing a synopsis of intraocular lenses which are being used in the present practice. The types have been classified based on structure, sites of fixation, optic and haptic material, Focality and also asphericity. The article also emphasizes the IOLs which have special functions and are used in uncommon situations. Future designs and newer concepts are being introduced every year owing to the advancements in our field.